Beyond CTLA-4: novel immunotherapy strategies for metastatic melanoma. (March 2015) - Matikas, Alexios; Mavroudis, Dimitrios
ABSTRACT : The treatment of metastatic melanoma is rapidly evolving. The discovery of BRAF and MEK inhibitors was an important milestone. Unfortunately, although response rates are high, disease progression is universal. Despite the success of IL-2 and adjuvant IFL-α2b, these two agents remained the only approved immunotherapy approaches. In recent years, the use of immunotherapy has drawn attention with the recognition of the mechanisms of tumor immune evasion. Blockade of these mechanisms may improve outcomes. However, the potential adverse events, the optimal use of these modalities, the high cost and the absence of predictive markers remain unmet challenges. Herein, we review the immunotherapy strategies in melanoma, either approved or under evaluation, and present the relevant data concerning their efficacy and safety.